2008
DOI: 10.1016/j.ydbio.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Diet controls normal and tumorous germline stem cells via insulin-dependent and -independent mechanisms in Drosophila

Abstract: The external environment influences stem cells, but this process is poorly understood. Our previous work showed that germline stem cells (GSCs) respond to diet via neural insulin-like peptides (DILPs) that act directly on the germ line to upregulate stem cell division and cyst growth under a protein-rich diet in Drosophila. Here, we report that DILPs specifically control the G2 phase of the GSC cell cycle via phosphoinositide-3 kinase (PI3K) and dFOXO, and that a separate diet mediator regulates the G1 phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
211
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(230 citation statements)
references
References 68 publications
17
211
0
Order By: Relevance
“…High levels of CYE-1 are also observed in other rapidly dividing cells that lack a significant G1 phase, including mouse embryonic stem cells (Stead et al, 2002) and early Drosophila and Xenopus embryos (Richardson et al, 1993;Rempel et al, 1995). Importantly in Drosophila, the male germline stem cell/cystoblast daughter lacks a detectable G1 phase under normal conditions (Yukiko Yamashita, personal communication), and the female germline stem cell has a short G1 with high cyclin E in G2 and M phase (Hsu et al, 2008). Thus, an atypical cell cycle structure with a short or no G1 and high cyclin E levels may be common in germline stem cell systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of CYE-1 are also observed in other rapidly dividing cells that lack a significant G1 phase, including mouse embryonic stem cells (Stead et al, 2002) and early Drosophila and Xenopus embryos (Richardson et al, 1993;Rempel et al, 1995). Importantly in Drosophila, the male germline stem cell/cystoblast daughter lacks a detectable G1 phase under normal conditions (Yukiko Yamashita, personal communication), and the female germline stem cell has a short G1 with high cyclin E in G2 and M phase (Hsu et al, 2008). Thus, an atypical cell cycle structure with a short or no G1 and high cyclin E levels may be common in germline stem cell systems.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, nutrient deprivation is not the signal for meiotic entry. Instead, nutrient deprivation can affect the rate of stem cell proliferation, at least in part through insulin signaling (Drummond-Barbosa and Spradling, 2001;Hsu et al, 2008;Michaelson et al, 2010), with meiotic entry controlled by developmental pathways (Crittenden et al, 2002;Hansen et al, 2004b;Matson et al, 2010). Nevertheless, in animals, control of the mitotic cell cycle and core cell cycle regulators is also likely to be important in the switch from proliferation to meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,21 The O. dioica Cyclin D variants, Da, Db, Dc and Dd are encoded by 4 different genes. 24 Previously, we have shown that O. dioica Cyclin Dd regulates G1-phase in mitotically proliferating cells during early development and in post-metamorphic somatic endocycling cells.…”
Section: Asynchronously Proliferating O Dioica Germ Nuclei Have a DImentioning
confidence: 99%
“…In invertebrate Drosophila and C. elegans GSCs, G1 phase is nearly absent. [18][19][20][21] In this context, cell cycle profiles of Cyclin E-CDK activity are altered with Cyclin E present throughout the GSC cell cycle. 18,21 In these invertebrates, proliferative renewal of GSCs is nonetheless still responsive to insulin and TOR signaling 2,22 but these nutrient-dependent controls operate during G2, as opposed to G1.…”
Section: Introductionmentioning
confidence: 99%
“…Each GSC carries a unique organelle with a membranous-like structure, called a fusome, which is juxtaposed to the interface between the cap cell and the GSC. During the late G2/M, S, and early G2 phases of the GSC cell cycle, fusomes display a round, elongated, and exclamation point shape, respectively ( Figure 1B) [13,14]. A single GSC division gives rise to a cystoblast, which undergoes four rounds of incomplete division to form a 16-cell cyst; the cells of the cyst are interconnected with a branched fusome [12].…”
mentioning
confidence: 99%